2002
DOI: 10.1103/physrevb.65.094434
|View full text |Cite
|
Sign up to set email alerts
|

Spin and orbital effects of Cooper pairs coupled to a single magnetic impurity

Abstract: The Kondo effect strongly depends on spin and orbital degrees of freedom of unconventional superconductivity. We focus on the Kondo effect in uniformly gapped superconducting systems ͑the two-dimensional p x ϩip y -wave and d x 2 Ϫy 2ϩ id xy -wave superconductors here͒ to compare the magnetic properties of the spintriplet and spin-singlet Cooper pairs. The difference appears when both of the paired electrons couple to a local spin directly. For the p x ϩip y wave, the ground state is always a spin doublet for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We examine the magnetic impurity problem as in the d x 2 −y 2 + id xy -wave case. 26) In Fig. On the other hand, for a small T K /∆, the doubly degenerate bound (spin-singlet) state appears in the superconducting energy gap, like a nonmagnetic impurity in §2.…”
Section: Quantum Spin and Kondo Effectmentioning
confidence: 93%
See 1 more Smart Citation
“…We examine the magnetic impurity problem as in the d x 2 −y 2 + id xy -wave case. 26) In Fig. On the other hand, for a small T K /∆, the doubly degenerate bound (spin-singlet) state appears in the superconducting energy gap, like a nonmagnetic impurity in §2.…”
Section: Quantum Spin and Kondo Effectmentioning
confidence: 93%
“…It was found that low energy states appear with four-fold symmetry near the impurity. [18][19][20][21][22] About a single magnetic impurity, we previously investigated a quantum spin in unconventional superconductors using the NRG method and focused on a fully gapped chiral superconductor expressed by p x ± ip y -wave or d x 2 −y 2 ± id xy -wave type order parameters, [23][24][25][26][27] where orbital effect of the Cooper pair plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al have studied the isotropic high-spin impurities in a side-coupled configuration 48 and the two-level impurity model 49 . The twochannel models have been studied in the context of unconventional superconductors 50 and iron pnictide superconductors 51 . Moca et al have demonstrated the presence of multiple sub-gap states in a multi-orbital model for Mn impurity in MgB 2 52 .…”
Section: Stm Tipmentioning
confidence: 99%
“…A reliable theoretical tool is the numerical renormalisation group (NRG) 11,12,13 . The NRG has been applied, for example, to study the sub-gap bound states in isotropic 14 and anisotropic 15 Kondo model and in the Ander-son model 16 in both conventional and unconventional 17,18 superconductors. Further NRG calculations focused on dynamical properties such as the spectral function 19,20,21,22 and more recently on the transport properties of quantum dots attached to superconducting leads 23,24,25,26,27 .…”
Section: Introductionmentioning
confidence: 99%